The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5152/iao.2019.6257
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Persistent Tinnitus and Dizziness in an Elderly Population in Southern Taiwan

Abstract: The Journal of International Advanced Otology (J Int Adv Otol) is an international, peer reviewed, open access publication that is fully sponsored and owned by the European Academy of Otology and Neurotology and the Politzer Society. The journal is published triannually in April, August, and December and its publication language is English. The scope of the Journal is limited with otology, neurotology, audiology (excluding linguistics) and skull base medicine. The Journal of International Advanced Otology aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 28 publications
3
26
0
6
Order By: Relevance
“…Similarly, proactive training can also enhance or maintain performance and normal processing (e.g., Anderson et al, 2013). Tinnitus and dizziness are related to hearing health and negatively affect the quality of life (Grauvogel et al, 2010;Miura et al, 2017;Chang et al, 2019). We did not observe a prevalence difference across age groups for tinnitus as has been reported by other authors (Sindhusake et al, 2003;McCormack et al, 2016) or was there an indication that tinnitus increases with age as suggested by Al-Swiahb and Park (2016) and reviewed by McCormack et al (2016).…”
Section: Functional Benefits Of Cochlear Implantationsupporting
confidence: 62%
“…Similarly, proactive training can also enhance or maintain performance and normal processing (e.g., Anderson et al, 2013). Tinnitus and dizziness are related to hearing health and negatively affect the quality of life (Grauvogel et al, 2010;Miura et al, 2017;Chang et al, 2019). We did not observe a prevalence difference across age groups for tinnitus as has been reported by other authors (Sindhusake et al, 2003;McCormack et al, 2016) or was there an indication that tinnitus increases with age as suggested by Al-Swiahb and Park (2016) and reviewed by McCormack et al (2016).…”
Section: Functional Benefits Of Cochlear Implantationsupporting
confidence: 62%
“…In the Korean population, the prevalence of tinnitus increased sharply after 55 years of age and peaked at 70 (1). In south Taiwan, Chang et al reported a 32% prevalence of persistent tinnitus among people older than 65 years (6).…”
Section: Introductionmentioning
confidence: 99%
“…Tinnitus is defined as a phantom auditory perception without external sound stimulation. Tinnitus is common in otolaryngology, with a prevalence rate of 10–15% in adults ( Henry et al, 2020 ) and about 32.0% in an elderly population ( Chang et al, 2019 ). Bothersome tinnitus can cause mood disorders like depression, anxiety, and also leads to sleep disorders.…”
Section: Introductionmentioning
confidence: 99%